Chemical Properties of Liquid Broth Extracted from Freshwater and Marine Shrimp Shells Waste - Fadhallah, Esa Ghanim; Koesoemawardani, Dyah; Indraningtyas, Lathifa (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Indonesia's shrimp industry is growing rapidly, but a surge in shrimp waste such as shells and heads’ shrimps are increasing as well. These waste products contain important components such as protein, minerals, and amino acids. This study aims to determine the chemical properties of liquid broth extracted from freshwater and marine shrimp shells, including ash, protein, fat, monosodium glutamate (MSG), and antioxidant. The liquid broth was extracted by boiling shrimp shells and heads in water with a ratio of 1:2 for 1 hour at 80oC. Results indicate that the type of shrimp used did not affect the broth's ash, fat, protein, MSG, or antioxidant content. Marine and freshwater shrimp liquid broths contain 0.56% and 0.28% ash, 0.10% and 0.50% fat, 2.19% and 1.97% protein, 1.5291% and 1.6274% MSG, and 2263.73 ppm and 2786.2 ppm antioxidant.